Intestinal graft versus host disease. Issue 10 (October 1991) - Bryan, R L; Antonakopoulos, G N; Newman, J; Milligan, D W
Abstract : An ileocolectomy specimen was examined from a patient with graft versus host disease (GvHD). In addition to the characteristic histological features of this condition, both the small and the large intestine showed extensive destruction of mucosal tissue with survival of clusters of enterochromaffin cells. This appearance has previously been described only in the large bowel. Endocrine cells seem to be less vulnerable to the effects of GvHD than epithelial cells, resulting in their being spared, which is not seen in other types of crypt destruction.